Capacidade de combinação e divergência genética de linhagens de tomateiro com aptidão industrial - Figueiredo, Alex Sandro Torre (2013)
The objective of this study was to estimate and correlate the ability to combination (CGC and CEC) of lines industrial tomato with genetic divergence in the genitors, estimated through morphological and molecular markers (ISSR). Was used as genitors, ten lineages tomato the genebank granted by the of the Research Center for Vegetables (NUPH) State University Midwestern - UNICENTRO. Conducted to field a diallel mating with parents and F1 hybrids, excluding the the reciprocal effects (Griffing, 1956). The complete diallel been installed in horticulture sector in NUPH under an experimental-type randomized blocks containing 57 genotypes (treatments) (ten parents, 45 F1 hybrids experimental and two commercial checks) repeated thrice. Were evaluated 25 traits related to morphology, production cycle and postharvest quality of fruits. Was estimated CGC for the parents as well as the CEC and heterosis for hybrids. Was also estimated the genetic divergence of parents on the basis of morphoagronomic traits and molecular. Parents were clustered according to the genetic divergence by UPGMA method, and these values estimated by the generalized Mahalanobis distance (agronomic traits) and Jaccard (molecular information). Results showed that non-additive effects were predominant for the traits related to fruit production and pulp yield. Lineage RVTD-2009-08 is the most appropriate for breeding programs intrapopulational, since they have high estimates of CGC. The hybrid-RVTD 2009-08 RVTD x-2009-09 and 2009-07 RVTD-x-RVTD 2009-10 have great potential for obtaining segregating populations, with later selection of elite lines for yield characteristics and pulp yield, addition to being experimental hybrids were superior, differing from the commercial checks. They both markers were effective at estimate the genetic divergence of parents, lineage classifying RVTD 2009-08 as the most divergent of the parent study. The lowest estimate of genetic similarity obtained by Mahalanobis and Jaccard was observed in the hybrid-RVTD 2009-08 RVTD x-2009-09, which also showed the highest estimates of specific combining ability, heterosis and general average for several important traits. There was no significant correlation between measures of genetic divergence with estimates of specific capacity, and average heterosis genotypes.